Liquefaction potential study under Ijo Balit weir in East Lombok Indonesia - Burhan, Lalu Ibrohim; Artati, Hanindya Kusuma; Makrup, Lalu; Saputra, Elvis (Teknisia, 2025)
Liquefaction phenomenon can be occurred in the sandy soil. Caused by an earthquake shaking on the sandy soil so the shear stress of the soil will be lost and the soil seem like liquid. Liquefaction in a site can cause the building on soil surface in the site can be crack or collapse. Therefore, it is need to study to review the liquefaction potential that will be occurred under Ijo Balit weir East Lombok. In general, the liquefaction, trigger by the earthquake shaking. Based on this condition so can be developed the earthquake shaking in form of the earthquake acceleration for time history. The time history of the earthquake wave can be developed in ground surface based on the spectral-matching-procedure with the target spectrum is design spectrum. Based on ground surface time history then can be calculated liquefaction potential on the soil layer under the Ijo Balit weir East Lombok. The study result can be mention that the soil layer in the site is not experience liquefaction.